Consequences of Measurement Error for Inference in Cross-Lagged Panel Design—The Example of the Reciprocal Causal Relationship Between Subjective Health and Socio-Economic Status. (15th September 2015) - Kröger, Hannes; Hoffmann, Rasmus; Pakpahan, Eduwin
Abstract : We discuss the problem of random measurement error in two variables when using a cross-lagged panel design. We apply the problem to the question of the causal direction between socio-economic status and subjective health, known also as health selection versus social causation. We plot the bias of the ratio between the social causation and the health selection coefficient as a function of the degree of measurement error in subjective health and socio-economic status for different scenarios which might occur in practice. Using simulated data we give an example of a Bayesian model for the treatment of measurement error that relies on external information about the degree of measurement error.